2004
DOI: 10.1139/v04-123
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase oxidation of benzene to phenol by copper catalysts in aqueous solvent with a high acetic acid concentration

Abstract: The liquid-phase catalytic oxidation of benzene was carried out under mild reaction conditions over Cuimpregnated zeolite catalysts (Cu/NaX, Cu/HX, Cu/NaY, Cu/HY, Cu/NaZSM-5, Cu/HZSM-5, Cu/Namordenite, Cu/Hmordenite, and Cu/Hbeta) using both molecular oxygen and ascorbic acid as the oxidant and the reducing reagents, respectively. Phenol was exclusively produced as the oxidation product and no other product was detected. Among the catalysts tested in this study, the Cu/HY catalyst had the highest activity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…However, a drawback in the supported Cu-ascorbic acid-O 2 catalytic system is that the catalytic activity for phenol formation stops during the initial stage of the oxidation [6,7]. Part of the Cu species on the supported Cu catalyst was observed to leach into the reaction solution during the initial stage of the phenol formation [8]. The eluted Cu species once again rapidly precipitated followed by deactivation of the phenol formation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a drawback in the supported Cu-ascorbic acid-O 2 catalytic system is that the catalytic activity for phenol formation stops during the initial stage of the oxidation [6,7]. Part of the Cu species on the supported Cu catalyst was observed to leach into the reaction solution during the initial stage of the phenol formation [8]. The eluted Cu species once again rapidly precipitated followed by deactivation of the phenol formation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Part of the Cu species on the supported Cu catalyst was observed to leach into the reaction solution during the initial stage of the phenol formation [8]. The eluted Cu species once again rapidly precipitated followed by deactivation of the phenol formation [8]. The amount of Cu precipitate has been reported [9] to be correlated to the yield of phenol, thus the precursor of the Cu precipitate is thought to be an active Cu species for the benzene oxidation to phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Kitamura et al investigated the benzene oxidation to phenol in aqueous solutions on several copper impregnated zeolites [1]. In this study the HY-zeolite showed the highest catalytic activity for the benzene conversion with a reported selectivity towards phenol of 100% but with a phenol yield of only 2.5%.…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, these observations indicate that phenol formation in the gas phase reaction can occur by a different reaction mechanism than in aqueous solution [1,9].…”
Section: The Role Of Coppermentioning
confidence: 95%
“…Gas-phase catalytic oxidation of benzene to phenol over copperimpregnated HZSM-5 catalysts [3] and the liquid phase oxidation of benzene over impregnated zeolite catalysts (Cu/NaX, Cu/HX, Cu/HY, Cu/NaZSM-5, Cu/Namordenite, Cu/Hmordenite and Cu/Hbeta) were some of the recent reports [4]. The oxidation of benzene to phenol using transition metal substituted polyoxometastable compounds in the presence of acetone and sulfonate [5] and V/Al 2 O 3 -SiO 2 catalysts [6] containing around 80% acetic acid and CuO/Al 2 O 3 catalysts [7] prepared by the co-precipitation method was also reported.…”
Section: Introductionmentioning
confidence: 99%